Mining, Society, and a Sustainable World - Richards, Jeremy (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This is the first book of peer-reviewed, edited papers that examines the broad subject of the minerals industry in relation to sustainable development. The book takes a proactive, positivist, and solution-oriented approach, while not shying away from identifying the real problems that mining raises in respect to social and economic development, environmental impact, and human development in general.